Using simulation and lab validation to develop a MnCO3 Recovery Process using CO2 - Sibanda, Thabo (Department of Chemical Engineering, 2026)
Manganese (Mn) is a critical metal in the production of lithium-ion battery (LiB) precursors due to its role in improving safety, stability and promoting higher efficiency and faster charging of LiBs. Battery-grade Mn or High Purity Manganese Sulphate Monohydrate (HPMSM, MnSO4·H2O), a key LiB precursor, requires low Mg and Ca content (< 0.01 wt.% each). Industrial MnSO4 pregnant leach solutions are a valuable source of HPMSM but conventional purification using electrowinning is energy-intensive, unsustainable, and environmentally harmful. Therefore, this study aimed to investigate the feasibility of chemical precipitation using a greenhouse gas (carbon dioxide gas, CO2) and ammonia (NH3) as a sustainable and cheaper alternative purification method. A high-concentration industrial MnSO4 pregnant leach solution containing at least 93.9 wt.% Mn2+, 2.23 wt.% Mg2+, and 0.14 wt.% Ca2+ was used. The results on the effect of pH from thermodynamic simulations were compared to experimental results. Experimental results investigated the effect of pH from 5.0 to 6.6 and CO2 bubbling times from 1 to 12 h using a 1.0 L semi-batch and continuously stirred glass reactor at ambient temperature and pressure. The CO2 was sparged at 0.4 L/min and the agitator speed was 500 rpm. The thermodynamic simulation predicted more than 94% Mn2+ recovery at pH > 5.0, with optimal Mn2+ selectivity at pH < 6.6. The experimental results showed optimal Mn2+ recovery of 61.3% at pH 6.6 and 8 h CO2 bubbling time, with the rejection of 57.6% Mg2+ and 46.3% Ca2+ from the MnCO3 precipitate, respectively. The discrepancy between simulation and experimental results was attributed to the slow dissolution rate of CO2. Finally, regardless of the CO2 bubbling time and pH, the washed MnCO3 precipitate contained at least 98.8% Mn, 0.15% Ca, and 0.05% Mg, meeting high-purity Mn specifications, but slightly lower than the requirements for battery grade Mn (> 99.9 wt.%, ultra-high-purity). The CO2 bubbling time and pH have a significant influence on both the recovery of Mn2+ and the rejection of Mg2+ and Ca2+. It is recommended that future work to explore the influence of pH 6.6-7.0, the effect of increasing partial pressure of CO2, and the use of nanobubbles to enhance the CO2 absorption. This study showed that carbonate precipitation using CO2 and NH3 can selectively recover Mn2+ from an industrial MnSO4 leachate containing high Mg2+ and Ca2+ impurities, offering a sustainable process with great potential for industrial application.